Rabies: Is it Possible to Treat? - Basher, Ariful (Bangladesh Journal of Medicine, 2024)
Rabies is one of the oldest and deadliest diseases in the world and causes a significant number of deaths. Over 95% of all human deaths from rabies occur in Asia and Africa. Bangladesh is endemic to rabies. Since the National Rabies Elimination Program was successfully implemented in 2010, Bangladesh has achieved considerable strides in preventing human mortality from rabies. Rabies post-exposure prophylaxis (PEP) is widely used and very effective. However, occasional incidences of rabies in individuals who have initiated or completed PEP have been documented. In this observational cohort study, total 45 clinically diagnosed rabies patients, irrespective of age and gender, from 33 different districts of Bangladesh were studied. A detailed clinico-demographic profile, including post-exposure prophylaxis received before the development of rabies, was recorded. RT-PCR for rabies was done on the saliva samples of all patients. An MRI, EEG, and CSF viral panel were also done for patients who were RT-PCR negative. From January 2022 to June 2023, 45 clinically diagnosed rabies cases were admitted to IDH. Two of them were PCR-positive. The median age of the patients was 11 years (IQR 5–40 years). 37 (82.2%) were males. Dogs were the most commonly accused animal (86.5%). The median time from exposure to the development of rabies symptoms was 37 days (IQR 22–60 days, range 07–240 days). The median duration of illness was 5 days (IQR: 3–7 days). All of the patients had severe exposure. Only 5(11%) patients received complete WHO-recommended post-exposure prophylaxis (PEP). 20 (45%) patients received only the rabies vaccine (incomplete PEP) without a wound wash or RIG. All the patients received supportive management. In addition to that, three patients were given intrathecal RIG at 40 U/kg/dose for two doses seven days apart. Out of three patients, two survived for more than two months. One patient is still alive after six months with significant morbidity. There is no cure for rabies; however, appropriate animal bite management by trained medical personnel with WHO-recommended PEP is the only way to achieve the goal of a rabies-free world. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 140